Biorredução de cetonas aromáticas pró-quirais e outros compostos carbonilados utilizando as sementes de Sinapis alba l. (mostarda amarela) - Sousa, Emerson Yvay Almeida de (2017)
The present study investigated the seeds of the vegetable Sinapis alba in order to verify its biocatalytic potential in reactions of reduction of aromatic ketones and aldehydes, among other carbonylated compounds, as well as to verify the presence of fatty acids in the fixed oil. In the first case, regarding ketones, the objective was to obtain enantiomerically pure alcohols and, in the second case, to identify the fatty acids. Initially the soluble protein content was determined by the Bradford method. This relatively high content (110 g / L) demonstrated the possibility of the presence of enzymes in the plant material and indicated its potential as a biocatalyst source. Then, using acetophenone as a model substrate, reduction reactions were performed to optimize the reaction parameters in obtaining the 1-phenylethanol product, in order to obtain a higher yield and a higher enantiomeric excess. The reaction parameters studied were: amount of biocatalyst, reaction time, speed of rotation, temperature, use of co-solvent, buffering medium (pH) and use of polyvinylpyrrolidone (PVP). Reactions were conducted in aqueous medium using buffer solutions at pH 6.0 and pH 6.5 / PVP. The best results were obtained at pH 6.0 with conversion of 69.8%, while the best enantiomeric excess (61.2%) for the S-isomer was achieved by the use of the co-solvent isopropanol. Further reduction reactions were performed from acetophenone derivatives (2-methyl-acetophenone, 2-methoxyacetophenone, 3- methoxyacetophenone, 3-nitro-acetophenone, 4-nitro-acetophenone, 4-fluoroacetophenone and 4-bromoacetophenone), but also from benzaldehyde and some of its derivatives, among others. The quantification of the conversion rates was performed by Gas Chromatography coupled to Mass Spectrometry (GC / MS) and the enantiomeric excess was performed by High Efficiency Liquid Chromatography (HPLC) using chiral OD-H and OB-H columns.